Comprehensive Surgical Approaches for Paralytic Esotropia - Widayanto, Fredy; Loebis, Rozalina (Vision Science and Eye Health Journal, 2025)
Introduction: Paralytic esotropia occurs due to paralysis of the lateral rectus muscle due to sixth nerve paralysis. One of the etiologies of sixth nerve palsy is trauma. Examination and holistic management should be done in patients with sixth nerve palsy, as this condition will have a psychosocial impact on the patient. In this case series, the authors will report on the different approaches to comprehensive management in paralytic esotropia cases. Case Presentation: The first patient had 30Δ paralytic esotropia in the right eye for ten months after an accident, experiencing diplopia in the primary gaze worsening in the left gaze, with abduction limitation. He underwent a 7 mm medial rectus recession as the first step, followed by vertical rectus transposition with Foster modification after three months. This treatment successfully restored orthophoria with no diplopia in the primary gaze. The second patient developed paralytic esotropia (10) after a traffic accident one year prior, with minimal motility limitation. He underwent a 4 mm medial rectus recession, restoring binocular vision and allowing him to return to work. Conclusion: Sixth cranial nerve paralysis is the most common cause of eye-related nerve paralysis, leading to loss of lateral rectus muscle function, diplopia, and significant psychosocial impacts. Surgical treatment for chronic paralytic esotropia depends on the severity of muscle weakness, with different procedures recommended based on the ability of the lateral rectus to contract. Case studies showed that appropriate surgical interventions, such as medial rectus recession and vertical rectus transposition, effectively managed the condition and improved patient outcomes.